(untitled) (Revista Sistemas de Producción Agroecológicos, 2015)
A summary of the main obstacles to efficiently enhance livestock in Colombia and Latin America is performed. The development of livestock in their current circumstances and future expectations that have generated the appreciation of natural resources taking into account the increase in exports of their products in the past 10 years, which could become a factor of economic development is analyzed. In response to environmental challenge that generates increased livestock production, particularly as regards deforestation rates are showing some changes toward more intensive systems combined crop and livestock production more milk. All this is due to: investments in transportation infrastructure, land conversion grazing on farmland and the rapid increase in per capita consumption of meat and milk has been accompanied by a shift in the sources of calories and protein, replacing meat red by poultry. The trend toward more intensive livestock production is making the region one of the most sensitive in the world in terms of health risks to animals could therefore be concluded that the discrepancy between livestock development and its environmental impact requires a strong but balanced approach, considering investments in research, prevention and eradication, education and training and a series of measures to improve productivity and profitability of the activity.